2023
DOI: 10.3389/fgene.2023.1101397
|View full text |Cite
|
Sign up to set email alerts
|

Analysis in Proceratophrys boiei genome illuminates the satellite DNA content in a frog from the Brazilian Atlantic forest

Abstract: Satellite DNAs (satDNAs) are one of the most abundant elements in genomes. Characterized as tandemly organized sequences that can be amplified into multiple copies, mainly in heterochromatic regions. The frog P. boiei (2n = 22, ZZ♂/ZW♀) is found in the Brazilian Atlantic forest and has an atypical pattern of heterochromatin distribution when compared to other anuran amphibians, with large pericentromeric blocks on all chromosomes. In addition, females of Proceratophrys boiei have a metacentric sex chromosome W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Comparative analyses between the sexes have demonstrated that satellite DNAs are of great importance for the differentiation of sex chromosomes [16,26,27,[68][69][70][71][72][73]. The Z and W chromosomes of all birds are descended from the same ancestral autosomal pair, most likely between 60 and 100 million years ago [74].…”
Section: Discussionmentioning
confidence: 99%
“…Comparative analyses between the sexes have demonstrated that satellite DNAs are of great importance for the differentiation of sex chromosomes [16,26,27,[68][69][70][71][72][73]. The Z and W chromosomes of all birds are descended from the same ancestral autosomal pair, most likely between 60 and 100 million years ago [74].…”
Section: Discussionmentioning
confidence: 99%
“…A similar scenario has already been reported in other animal species, such as the frog Proceratophrys boiei . Despite having a simple and heteromorphic ZZ/ZW sex chromosome system, it is distinguished by the absence of sex-specific satDNAs and low sex divergence, indicating their early stage of sex chromosome differentiation [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…This approach has allowed the characterization of satDNAs in the genomes of numerous non‐model species from different groups. For example, satDNAs have been studied in insects (Anjos et al, 2023; Cabral‐de‐Mello et al, 2021; Mora et al, 2020; Pita et al, 2017), mollusks (Tunjić‐Cvitanić et al, 2021), fishes (Goes et al, 2022; Kretschmer et al, 2022), frogs (da Silva et al, 2020; da Silva et al, 2023), mammals (Gutiérrez et al, 2022) and plants (Heitkam et al, 2021; Sader et al, 2021). Consequently, low‐abundance satDNAs have been characterized, and some of them have been found in euchromatin (Cabral‐de‐Mello et al, 2021; Milani et al, 2021; Montiel et al, 2021; Pita et al, 2017).…”
Section: Introductionmentioning
confidence: 99%